Peningkatan Kemampuan Siswa Menulis Paragraf Ekspositoris dengan Menggunakan Strategi Active Knowledge Sharing di Kelas XI SMK Negeri 1 Afulu - Lestari Waruwu; Imansudi Zega (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Discourse is: the most complete unit of language formed from a series of continuous, cohesive and coherent sentences according to the context of the situation. This study aims to improve students' ability to write Expository Paragraph Discourse by using an Active Knowledge Sharing strategy, especially for class XI students of Office Administration Department, SMK Negeri 1 Afulu.To achieve this goal, this study used the Classroom Action Research (PTK) method with the following procedures: (1) Planning, (2) Action, (3) Observation, (4) Reflection.This research was conducted in two cycles, and used data collection techniques, observation sheets, and assessment sheets. Data were analyzed in three stages, namely (1) data reduction, (2) data exposure, (3) conclusion. From the results of this study it was proven that there was an increase in students' ability to write expository paragraph discourse, in the first cycle the average student score was 53.5, while in the second cycle it reached 80.75.Based on the results of research in the field, it can be concluded that using the Active Knowledge Sharing strategy can improve the ability of class XI students of the Department of Office Administration, SMK Negeri 1 Afulu, in writing expository paragraph discourse. Based on these conclusions, the recommended suggestions are (1) The results of this study can be used as input and material for consideration for Indonesian language teachers. (2) For future researchers, it is hoped that they will be more creative and innovative in finding various varied learning strategies so that students are actively involved in the learning process in class.